2020
DOI: 10.1891/jfcp-18-00049
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Using Social Media for Personal Finance

Abstract: This study was intended to find out whether social media could be a solution to improve personal financial literacy and ability. The authors examined the antecedents and consequences of using social media for personal finance with survey data from 359 individuals who used social media tools to view, learn, post, or ask for financial information or advice. They found that usefulness and compatibility were two reasons why people use social media for personal finance, while ease of use and concerns/risks were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…SNS users can make personal public profiles, interact with friends and meet other people based on shared interests (Pahlevan and Mura, 2019). Generally, the proper use of SNS can be rather beneficial as it provides users with a direct communication channel and allows them access to useful information that can assist them in gaining social support, achieving positive financial outcomes, decreasing loneliness and enhancing their well-being (Cao et al , 2020; Wang et al , 2014). However, some individuals lack self-control and may be driven by a strong desire to use SNS by devoting an excessive amount of time and effort, resulting in negative consequences related to cultural consumption and social comparison (Sharif and Khanekharab, 2017; Verduyn et al , 2020; Verduyn et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SNS users can make personal public profiles, interact with friends and meet other people based on shared interests (Pahlevan and Mura, 2019). Generally, the proper use of SNS can be rather beneficial as it provides users with a direct communication channel and allows them access to useful information that can assist them in gaining social support, achieving positive financial outcomes, decreasing loneliness and enhancing their well-being (Cao et al , 2020; Wang et al , 2014). However, some individuals lack self-control and may be driven by a strong desire to use SNS by devoting an excessive amount of time and effort, resulting in negative consequences related to cultural consumption and social comparison (Sharif and Khanekharab, 2017; Verduyn et al , 2020; Verduyn et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this, the interpretation can be made as the majority of the population who took up this survey is definitely into the idea of personal finance and the encouragement for small investments and for the generation of platforms for passive income apart from the main stream income is imperative and necessary (Förster et From the above data, we can assess that majority of the users have knowledge about personal finance and its uses. The users are very much inclined towards the idea of personal finance and the reliability on the concept which fetches them parallel stream of income (Cao et al, 2020;Navickas et al, 2014). Most of them feel passive income cloud help in supporting and managing their expenses which can divert their main stream income to the field of small investments though personal finance plans and ideas.…”
Section: Management Of Contingencies Challengesmentioning
confidence: 99%
“…The concept of personal finance is gradually reaching the pinnacle as there are lot of users who are abundantly into small investments. With the above data it can be interpreted that there is a lot of scope for small investments other the conventional investment methods and platforms like stock markets and mutual funds where usually investments are made with huge cash outflow and fund balance (Cao et al, 2020;Happ et al, 2018). The concept of personal finance helps in being an aid through small investments and fetched return on investments with no huge risk involved and can be an investment concept where people can confidently go ahead and invest and manage their funds effectively and efficiently to maximize their cash inflow and outflow which is a vital part of peoples' life.…”
Section: Management Of Contingencies Challengesmentioning
confidence: 99%
“…As such, it is important to acknowledge that fintech, while growing in prevalence, is not a replacement for financial literacy. Relatedly, Cao et al (2020) surveyed individuals using social media to view, learn, post, or ask for personal financial information and advice. Their study revealed that social media use for personal finance was associated with positive financial outcomes and user satisfaction, which in turn prompted users' intentions for continued use in the future.…”
Section: Financial Website/app Usagementioning
confidence: 99%